Langmuir and Langmuir-Blodgett films containing a porphyrin-ruthenium complex - Wohnrath, K.; Dinelli, L. R.; Mello, S. V.; Constantino, CJL; Leblanc, R. M.; Batista, A. A.; Oliveira, O. N. (Amer Scientific Publishers, 2005)
The fabrication of supramolecular structures from the tetraruthenated porphyrin-containing phosphines, {TPyP[RuCl3(dppb)](4)}, RuTPyP, is demonstrated with Langmuir and Langmuir-Blodgett films. The surface pressure-molecular area isotherms (pi-A) point to an edge-on arrangement for the RuTPyP molecules in the condensed state. Weak aggregation in the Langmuir films was indicated by non-zero surface potentials at large areas per molecule and a slight red shift in the ultraviolet-visible absorption spectrum in comparison to the spectrum in solution. Further aggregation occurs in the Z-type Lang muir-Blodgett films, which was confirmed with ultraviolet-visible spectroscopy of the deposited films. Fourier transform infrared and Raman spectroscopic data for powder and Langmuir-Blodgett films indicate that the RuTPyP molecules are chemically stable in Langmuir-Blodgett films regardless of the contact with water during film fabrication. The nanostructured nature of the Langmuir-Blodgett films was manifested in cyclic voltammetry due to the high sensitivity of the metallic centers in RuTPyR Electrodes modified with Langmuir-Blodgett films exhibit an anodic peak at 100 mV and a cathodic peak at 7 mV, which is assigned to RuIII/RuII redox processes. Furthermore, Langmuir-Blodgett films from RuTPyP showed electrocatalytic activity for oxidation of benzyl alcohol, illustrated by a large shift of 100 mV in the anodic peak at 400 mV, while electropolymerized and cast films of the same compound displayed smaller and no activities, respectively.
Keywords: porphyrin; Langmuir-Blodgett films; supramolecule; spectroscopy; sensor